Analytical review of the features of the professional and psychological selection of citizens of Ukraine for Security Forces of the Sector of Security and Defense of Ukraine - Kravchenko, К.; Sokolina, О.; Кравченко, Катерина; Соколіна, Ольга (Київський національний університет імені Тараса Шевченка, 2023)
The authors of the article analyzed the guiding documents of the security forces of the security and defense sector of Ukraine regarding the conduct of professional and psychological selection of candidates for military service to protect the territorial integrity and independence of Ukraine. The concept of professional and psychological selection and its components are defined. The problems of the peculiarities of professional and psychological selection in the Ministry of Internal Affairs of Ukraine (National Guard of Ukraine, National Police of Ukraine, State Border Service of Ukraine, and State Service for Emergency Situations), Security Service of Ukraine, and Armed Forces of Ukraine are considered. An analytical review of the features of the professional and psychological selection of Ukrainian citizens to the security forces of the security and defense sector of Ukraine made it possible to draw the following conclusions. Professional and psychological selection in the system of the Ministry of Internal Affairs ofUkraine has both its general common features and a sufficient number of differences, borrowing at least some of them will make it possible to improve the quality of professional and psychological selection of candidates for service in these and other security forces. A feature of professional and psychological selection for the Security Service of Ukraine is the availability of methods aimed at diagnosing interpersonal relationships (the methodfor determining social intelligence, in other words, determining the ability to predict the consequences of the behavior of others, is worth paying attention to). Professional and psychological selection in the Armed Forces of Ukraine needs improvement, which is a difficult task, taking into account a large number of military accounting specialties, as well as large losses in units that need not only quick but also high-quality replenishment (taking into account the full-scale invasion of the Russian Federation on the territory of Ukraine.

Проаналізовано керівні документи силових структур сектору безпеки та оборони України щодо проведення заходів професійно-психологічного відбору кандидатів на військову службу по захисту територіальної цілісності та незалежності України. Визначено поняття професійно-психологічного відбору (ППВ) та його складових. Розглянуто проблематику особливостей проведення ППВ у Міністерстві внутрішніх справ України (Національній гвардії України, Національній поліції України, Державній прикордонній службі України, Державній службі з надзвичайних ситуацій), Службі безпеки України та ЗС України. Аналітичний огляд особливостей ППВ громадян України до силових структур сектору безпеки та оборони України дав змогу зробити висновки. Професійно-психологічний відбір у системі Міністерства внутрішніх справ України має як свої загальні спільні особливості, так і достатню кількість відмінностей, запозичення деяких з них дасть змогу підвищити якість ППВ кандидатів для проходження служби у цих та інших силових структурах. Особливістю професійно-психологічного відбору до Служби безпеки України є наявність методик, спрямованих на діагностику міжособистісних стосунків (варта уваги методика щодо визначення соціального інтелекту, тобто визначення здатності передбачити наслідки поведінки інших). Професійно-психологічний відбір у ЗС України потребує вдосконалення, що є важким завданням, зважаючи на велику кількість військово-облікових спеціальностей, а також великі втрати в підрозділах, які потребують не лише швидкого, але й якісного свого поповнення (ураховуючи повномасштабне вторгнення Російської Федерації на територію України).
Аналітичний огляд особливостей професійно-психологічного відбору громадян України до силових структур сектору безпеки та оборони України
Keywords: професійно-психологічний відбір у ЗС України; професійно-психологічний відбір у Службі безпеки України; професійно-психологічний відбір у Міністерстві внутрішніх справ України; професійно-психологічний відбір у Національній гвардії України; професійно-психологічний відбір у Національній поліції України; професійно-психоло- гічний відбір у Державній прикордонній службі України; професійно-психологічний відбір у Державній службі з надзвичайних ситуацій; професійно-психологічний відбір громадян України; professional and psychological selection in the Armed Forces of Ukraine; professional and psychological selection in the Security Service of Ukraine; professional and psychological selection in the Ministry of Internal Affairs of Ukraine; professional and psychological selection in the National Guard of Ukraine; professional and psychological selection in the National Police of Ukraine; professional and psychological selection in the State Border Service of Ukraine; professional and psychological selection in the State Service for Emergency Situations